NUTRIENT PROFILE AND MANGROVE VEGETATION COMPOSITION IN THE COASTAL WATERS OF INDRAMAYU - Frederika, Yanthi Christin; Nurul Ihsan, Yudi; Riyantini, Indah (Hasanuddin University, 2021)
Indramayu is a regencyin West Java with a coastline length of ± 114 km bordering the Java Sea and has a mangrove forest covering an area of 4060.5 ha. A small part (27,58 ha) of this mangrove forest is located Karangsong Village, Indramayu regency. Karangsong Indramayu mangrove forest has 4 types of mangroves namely Avicennia marina, Rhizophora stylosa, Avicennia alba, Rhizophora mucronata, where A. marina and R. stylosa dominated the are. The purpose of this study was to obtain the profile of nutrients in the coastal waters of Indramayu, identify the composition of mangrove vegetation, and to analyze the relationship between nutrients and mangrove vegetation composition in the coastal waters of Indramayu. The method used in this study was a survey approach method, quantitative approach, and data gained were analyzed descriptively. The results showed that apart from dissolved oxygen, the temperature, salinity, and pH in the waters of Karangsong Indramayu were classified to follow the characteristics of mangrove growth. The substrates at the research site silty loam and silty clay loam. Nutrient content was in the range of 0.211 mg/L – 0.252 mg/L(nitrate), 0.135 mg/L – 0.277 mg/L (nitrites), 0.51 mg/L - 0.74 mg/L (ammonia), and 0.109 mg/L – 0.140 mg/L (phosphate). The relationship between mangrove composition and nutrient profiles was directly proportional, where less nutrient content showed a decrease in mangrove growth